Implementation of Game-Based Assessment Media 'SPEDU' to Measure Conceptual Understanding of Ecology and Biodiversity among 7th Grade Junior High School Students in Yogyakarta - Amalia Haq; Eka Dahliani; Laila Munazad; Nur Zamzam Yuniar Faisal; Maryati; Ismail Fikri Natadiwijaya (BIOEDUKASI: Jurnal Biologi dan Pembelajarannya, 2025)
This study aims to describe the effectiveness of using the game-based assessment media "SPEDU" (Spinner Education) in measuring and improving students’ conceptual understanding of ecology and biodiversity material among seventh-grade students at a public junior high school in Yogyakarta. The research method employed in this study is descriptive quantitative with a pre-experimental approach, using a one-group pretest-posttest design. The implementation of the SPEDU media improved students' conceptual understanding, with an average posttest score of 8.00. This indicates that the application of SPEDU had a positive effect in enhancing students' conceptual understanding of ecology and biodiversity. The standard deviation results also showed that the posttest scores were more homogeneous compared to the pretest scores, suggesting that SPEDU was effective in improving students' understanding more evenly across the class in this subject matter. In addition, N-gain analysis indicated that the N-gain score for the ecology and biodiversity content was in the high category (0.86). The results of the Paired Sample t-Test analysis also indicated a significant difference between the pretest and posttest scores, confirming that the use of SPEDU had a significant impact on improving students’ conceptual understanding. Therefore, SPEDU is effective as an engaging and enjoyable learning tool that encourages students to develop a deeper understanding of ecological and biodiversity concepts.